XSLT cookbook - Mangano, Sal (O'Reilly, 2005)
Forget those funky robot toys that were all the rage in the '80s, XSLT (Extensible Stylesheet Transformations) is the ultimate transformer. This powerful language is expert at transforming XML documents into PDF files, HTML documents, JPEG files--virtually anything your heart desires. As useful as XSLT is, though, most people have a difficult time learning its many peculiarities. And now Version 2.0, while elegant and powerful, has only added to the confusion. XSLT Cookbook, Second Edition wants to set the record straight. It helps you sharpen your programming skills and overall understa.